Gender analysis and gender roles in "The Egg and I" and "Anybody Can Do Anything" by Betty - Oláhová, Lenka (Univerzita Pardubice, 2014)
This work is aimed to explain the central importance of gender analysis and to investigate gender roles, social status and economic position of women in the United States of America in the first half of the 20th century. Another aim of this paper is to demonstrate representation of such roles and positions of women in two books by Betty MacDonald The Egg and I and Anybody Can Do Anything.
MacDonaldGender analýza a gender role v knihách Betty MacDonaldové "Vejce a já" a "Kdokoliv může dělat cokoliv"
Keywords: gender analýza; ženy; gender role; literatura; literární analýza; stereotypy; diskriminace; gender analysis; women; gender role; literature; analysis of literature; stereotypes; discrimination